2021
DOI: 10.1186/s12974-021-02116-z
|View full text |Cite
|
Sign up to set email alerts
|

The psychoactive drug of abuse mephedrone differentially disrupts blood-brain barrier properties

Abstract: Background Synthetic cathinones are a category of psychostimulants belonging to the growing number of designer drugs also known as “Novel Psychoactive Substances” (NPS). In recent years, NPS have gained popularity in the recreational drug market due to their amphetamine-like stimulant effects, low cost, ease of availability, and lack of detection by conventional toxicology screening. All these factors have led to an increase in NPS substance abuse among the young adults, followed by spike of ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 57 publications
0
6
0
3
Order By: Relevance
“…hBMVECs were plated (20,000/well) on collagen I coated 96-well electrode arrays (96W20idf, Applied Biophysics, Troy, NY, USA) and grown until confluent. Trans-endothelial electrical resistance (TEER) was measured at 2 kHz every 600 s using the Electrical Cell-Substrate Impedance Sensing (ECIS) system (Applied Biophysics, Troy, NY, USA) as described previously (Buzhdygan et al 2021 ). Cells were grown until a constant baseline resistance was obtained and then media was replaced with lack of growth factors.…”
Section: Methodsmentioning
confidence: 99%
“…hBMVECs were plated (20,000/well) on collagen I coated 96-well electrode arrays (96W20idf, Applied Biophysics, Troy, NY, USA) and grown until confluent. Trans-endothelial electrical resistance (TEER) was measured at 2 kHz every 600 s using the Electrical Cell-Substrate Impedance Sensing (ECIS) system (Applied Biophysics, Troy, NY, USA) as described previously (Buzhdygan et al 2021 ). Cells were grown until a constant baseline resistance was obtained and then media was replaced with lack of growth factors.…”
Section: Methodsmentioning
confidence: 99%
“…Alteration of the blood-brain barrier is a common effect of SCs consumption reflected in in vitro human models. The experiments conducted by Buzhdygan et al on the effects of mephedrone on human brain microvascular endothelial cells (hBMVEC) showed that the treatment with mephedrone caused a charge-dependent disruption of the endothelial barrier and an increase of barrier permeability [ 106 ], demonstrating the ability of mephedrone to regulate the tight junction complex.…”
Section: Resultsmentioning
confidence: 99%
“…To examine gene expression via qRT-PCR, total Ribonucleic acid (RNA) was isolated as previously described [ 29 , 30 ]. Briefly, 1 mL TRIzol reagent was added to isolated microvessel tissue to dissociate total RNA from the samples.…”
Section: Methodsmentioning
confidence: 99%
“…The paracellular permeability assay was conducted as previously described [ 30 ]. Briefly, cells were plated in 200 µL of EGM-2 media at a density of 20,000 cells per well on the apical portion of semi-permeable trans-well inserts (Fisher Scientific, 0.4 µm pore size).…”
Section: Methodsmentioning
confidence: 99%